Chinese Customer Law in Hong Kong - Sihombing, Judith (Journal of Malaysian and Comparative Law, 2019)
The areas which form the territory of Hong Kong, namely the island of Hong Kong, the territorial waters, Kowloon and the New Territories, came under the administration of the colony of Hong Kong at different times from 1841 onwards. In that year, the island of Hong Kong was ceded to Britain. Then, at the end of the Second Anglo-Chinese War (1856-1858) perpetual leases of the Kowloon Peninsula up to Boundary Street, and of Stonecutter's Island, were granted to Britain. By the Convention of Peking in 1860 these leases were ceded outright. The area known as the 'New Territories' [being the land north of Bcundary Street on the Kowloon Peninsula up to Shum Chun River and 235 islands] was leased to Britain in 1898 by the Second Convention of Peking for 99 years up to 30 June 1997. From 1 July 1997 the People's Republic of China resumed sovereignty over the whole of Hong Kong; Hong Kong is now known as the Special Administrative Region of the People's Republic of China.